MANHAJ AL-TAFSIR AL-MISBAH KARYA QURASY SHIHAB - Wahyu din; Tatang Muslim Tamimi (Bayani, 2022)
M. Quraish Shihab is an expert on tafsir, his greatest work of Tafsir is Tafsir al-Mishbah. In his discussion, tafsir al-Misbah begins with the letter, with explanations related to the main theme of the letter. This article aims to formulate a special method of tafsir al-Mishbah by M. Quraish Shihab. The method used is a descriptive analysis method that describes the study and the results of the analysis. The findings of this paper, show that the tafsir of Al-Mishbah has the view that the Qur`an as a unit of surahs and verses that are compatible. As well as having a special method with the following characteristics, the use of verses and hadith as the main basis in interpretation, the use of reason is widely limited in understanding the verses of the Qur'an, associating interpretation with various results of modern science, critical of Israel and non-Muslim opinions on the Qur`an, linking interpretation to the social life of society. The general method is to perform analysis in various aspects in sequence in accordance with the order of the verses in the mushaf, then the tafsir of al-Mishbah is categorized using the method of tahlily. The method of tahlily (analysis) is to interpret the verses of the Qur'an by displaying all aspects contained in the verses that are interpreted and explain the meanings covered therein in accordance with the expertise and inclination of the commentator who interprets the verses. . Determining the main theme/purpose of the surah and grouping the verses